Therapeutic Potential of Novel Twin Compounds Containing Tetramethylpyrazine and Carnitine Substructures in Experimental Ischemic Stroke. (13th December 2017) - Wang, Ziying; Zhou, Zhuanli; Wei, Xinbing; Wang, Mingwei; Wang, Bi-Ou; Zhang, Yanan; He, Xiaoting; Sun, Yu; Wang, Xiaojie; Sun, Mingcheng; Zhang, Yan; Gong, Xiaowei; et al.
Abstract : Although studies have seen dramatic advances in the understanding of the pathogenesis of stroke such as oxidative stress, inflammation, excitotoxicity, calcium overload and apoptosis, the delivery of stroke therapies is still a great challenge. In this study, we designed and synthesized a series of novel twin compounds containing tetramethylpyrazine and carnitine substructures and explored their therapeutic potential and mechanism in stroke-related neuronal injury. We first screened the neuroprotective effects of candidate compounds and found that among the tested compounds, LR134 and LR143 exhibited significant neuroprotection as evidenced by reducing cerebral infarct and edema, improving neurological function as well as blood-brain barrier integrity in rats after cerebral ischemia/reperfusion injury. We further demonstrated that the neuroprotective effects of compounds LR134 and LR143 were associated with the reduced inflammatory responses and NADPH oxidase- (NOX2-) mediated oxidative stress and the protection of mitochondria accompanied by the improvement of energy supply. In summary, this study provides direct evidence showing that the novel twin compounds containing tetramethylpyrazine and carnitine substructures have neuroprotective effects with multiple therapeutic targets, suggesting that modulation of these chemical structures may be an innovative therapeutic strategy for treating patients with stroke.